Two new species of Flintiella Angrisano 1995 (Trichoptera: Hydroptilidae: Stactobiini) from northern Brazil - de Liege Gama Neto, Jaime; Ribeiro, José Moacir Ferreira; Passos, Mahedy Araujo Bastos (Zootaxa, 2020)
Two new species of Flintiella Angrisano 1995 are described and illustrated from specimens collected with light traps in the states of Pará and Roraima, northern Brazil. Flintiella serrana sp. nov. can be distinguished from all other species in the genus by the subgenital plate with incised apex, and two pairs of ventral processes. Flintiella triaena sp. nov. is distinctive with no clearly similar congeners and can be distinguished from all known species in the genus by the trident-like subgenital plate in ventral view. Additionally, we record the genus Flintiella for the first time in Roraima State.